2016
DOI: 10.1063/1.4960983
|View full text |Cite
|
Sign up to set email alerts
|

Optical Tamm states in one-dimensional superconducting photonic crystal

Abstract: In this study, we investigate localized and resonant optical waves associated with a semi-infinite superlattice made out of superconductor-dielectric bilayers and terminated with a cap layer. Both transverse electric and transverse magnetic waves are considered. These surface modes are analogous to the so-called Tamm states associated with electronic states found at the surface of materials. The surface guided modes induced by the cap layer strongly depend on whether the superlattice ends with a superconductor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The transmission matrices of dielectrics A, B, C, D, E, F, G are indicated by M A , M B , M C , M D , M E , M F and M G with the specific expression equation (7). The reflection and transmission coefficients are calculated as [29]:…”
Section: Theoretical Model and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmission matrices of dielectrics A, B, C, D, E, F, G are indicated by M A , M B , M C , M D , M E , M F and M G with the specific expression equation (7). The reflection and transmission coefficients are calculated as [29]:…”
Section: Theoretical Model and Simulationmentioning
confidence: 99%
“…In general, because 1D PCLT has photonic band gaps (PBGs) [5], the electromagnetic waves (EWs) cannot propagate in the PBGs under normal conditions [6]. But numerous studies have shown that [7,8], under the condition of introducing appropriate defect layers, a passband at a specific frequency is created in the PBGs, in which EWs can propagate. This feature provides ideas for the implementation of logical operations.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, great interest has been paid to localized surface modes called Tamm states [15], which were originally discovered for electrons in condensed matter physics. Later, Tamm states have been extended to classical wave systems such as acoustics [16][17][18], photonics [19][20][21] and plasmonics [22].…”
Section: Introductionmentioning
confidence: 99%
“…Tamm states have also been investigated in systems containing a PC with a tunable cap layer adjacent to a uniform medium. Examples include PCs containing superconducting layers [13], systems containing metamaterials, both the PC layers [14,15] and the uniform medium [16], and systems with liquid crystal [17] and chiral [18] cap layers. In addition, OTSs have also been studied at a metal/PC interface [19][20][21].…”
Section: Introductionmentioning
confidence: 99%